Effects of frequent oil treatment on the performance of native growing rams under intensive management system (Bangladesh Veterinarian, 2011)
The effects of oral administration of seven mL soybeen oil/kg live weight (LW) on the performance and carcass characteristics of native ram. In a 162 days feeding trial, 18 growing native rams (9.4 ± 1.2 kg BW and 176 ± 5.6 d of age) were randomly allocated to three treatments (T0, control, T1, monthly infusion of oil and T2, fortnightly oil infusion group) with six replicates in each. All animals were fed roughage (Ad lib urea molasses straw, UMS) and concentrate (1.5% of body weight). After feeding and digestion trial, five animals in each group were slaughtered for carcass characteristics. During the trial, growth rate was significantly (P